Do different autumn-winter crops correlate with various times and doses of glyphosate in desiccation influence weed infestation in soybean crops? (Research, Society and Development, 2025)
The objective was to evaluate the composition of the weed community in soybean crops after different autumn/winter crops under different doses and times of glyphosate application before soybean sowing. The experiment was conducted at Embrapa Agropecuária Oeste, in Dourados MS. The treatments evaluated were: T1: area of brachiaria desiccated 5 days before soybean sowing - DAS, with 2 L ha-1 of glyphosate; T2: brachiaria desiccated 5 DAS with 4 L ha-1; T3: brachiaria desiccated 30 DAS with 2 L ha-1; T4: brachiaria desiccated 30 DAS with 4 L ha-1; T5: desiccated consortium 5 DAS with 2 L ha-1; T6: desiccated consortium 5 DAS with 4 L ha-1; T7: desiccated consortium 30 DAS with 2 L ha-1; T8: desiccated consortium 30 DAS with 4 L ha-1; T9: desiccated cowpea 5 DAS with 2 L ha-1; T10: desiccated cowpea 5 DAS with 4 L ha-1; T11: desiccated cowpea 30 DAS with 2 L ha-1; T12: desiccated cowpea 30 DAS with 4 L ha-1; T13: desiccated corn 5 DAS with 2 L ha-1; T14: desiccated corn 5 DAS with 4 L ha-1; T15: desiccated corn 30 DAS with 2 L ha-1; T16: desiccated corn 30 DAS with 4 L ha-1. There were differences in weed diversity and infestation. Treatments with desiccation at 30 DAS showed greater dry mass among weed species. In short, in early desiccation there is a greater infestation of weeds, especially where there was cowpea and single corn as the predecessor crop at the lowest desiccation dose.